Anatomical study of surgical approaches for minimally invasive transoral thyroidectomy: eMIT and TOPP. Issue 6 (2nd November 2015) - Cai, Chengzhong; Huang, Yixiang; Zhang, Ti; Chai, Li; Wang, Gang; Shi, Linxiang; Wiegand, Susanne; Güldner, Christian; Günzel, Thomas; Wilhelm, Thomas
Abstract: Objective : Anatomical study of surgical approaches of endoscopic minimally invasive thyroidectomy (eMIT) and transoral partial parathyroidectomy (TOPP) was conducted to evaluate their safety and feasibility.Material and methods : After performing an eMIT- and TOPP-procedure on fresh frozen human cadavers, a layer-by-layer dissection of the floor of the mouth and the anterior cervical region was carried out in five specimens. The blood vessels, nerves and muscles related to the surgical approach were exposed.Results : The anterior region of the neck can be reached through the midline of the mouth floor and the suprahyoid muscles. No important nerves and vessels were found in the approach of eMIT. TOPP set up the space at the dorsal side of the thyroid gland and adjacent to the trachea. The hypoglossal nerve and the lingual nerve as well as their accompanying blood vessels were anatomically related to the approach and could be injured during the procedure. The surgical space is much limited in TOPP (<20 mm in diameter) and current surgical instruments still did not match the requirement of this technique.Conclusions : This study demonstrated that the transoral approach of eMIT is anatomically safer and more feasible than that of TOPP.